EFEKTIVITAS PENERAPAN STANDAR OPERASIONAL PROSEDUR PENERBITAN REKOMENDASI ANALISIS DAMPAK LALU LINTAS DINAS PERHUBUNGAN KOTA DEPOK - Tinan Wirawan; Yusyanah (Jurnal Ilmu Administrasi Publik, 2025)
This thesis discusses the Effectiveness of Implementing Standard Operating Procedures for Issuing Recommendations for Traffic Impact Analysis at the Depok City Transportation Agency. This study used a qualitative descriptive method by gathering information through interviews, observation and documentation. The results of this study indicate the standards applied by the Depok City Department of Transportation in issuing reliable traffic permits, such as time, information disclosure and technical services in providing recommendations. Based on the stages of work procedures that have been determined by the Department of Transportation, they have implemented and implemented service procedures properly, only information disclosure and transparency and procedure clarity are needed, so that permit applicants know the technical standards of the services provided. Keywords Effectiveness, SOP, Public Service